Public low-carbon related characteristics and their (dis)approval of nuclear energy in China against the backdrop of climate change: an analysis of influence mechanism - Su, Hongyan; Guo, Xiaodan; Wang, Jing (Frontiers in Environmental Science, 2025)
Developing nuclear energy is a controversial issue despite its inherently low-carbon emissions life cycle. Considering low-carbon awareness, perception of barriers and low-carbon behaviors as important personal characteristics in the context of climate change, then how these characteristics will affect people’s acceptance of nuclear energy? In this study, we explore the public low-carbon characteristics in China based on the latest representative national survey. The influence mechanism of individuals’ low-carbon behaviors is analyzed by structural equation model (SEM). Then, we explore how the individuals’ low-carbon characteristics relate to their attitudes toward nuclear energy. The results suggest that Chinese public has high low-carbon attitudes and values. However, lack of low-carbon knowledge, more perception of barriers and accordingly fewer low-carbon behaviors are still serious issues among the general public in China. Special attention should be given to the awareness–behavior gap, which can be mainly attributed to the existence of some barriers to performing low-carbon actions. Our survey suggests a higher proportion of people (approximately 88%) accepts nuclear energy development given some compensation. Perception of barriers and low-carbon habits are identified as important personal characteristics that can affect people’s attitudes toward nuclear energy. To smooth the development of nuclear power, the government should help the general public to possess more knowledge on nuclear energy and climate change.